1980
DOI: 10.3758/bf03197783
|View full text |Cite
|
Sign up to set email alerts
|

Fear of snakes in wild- and laboratory-reared rhesus monkeys (Macaca mulatta)

Abstract: Experiment 1 compared the responses of 10 laboratory-reared and 10 wild-reared rhesus monkeys iMacaca mulattai to a real snake and to a range of snake-like objects. Most wildreared monkeys showed considerable fear of the real. toy, and model snakes, whereas most lab-reared monkeys showed only very mild responses. Fear was indexed by unwillingness to approach food on the far side of the snake and by behavioral disturbance. Experiment 2 examined the effectiveness of seven flooding sessions in reducing snake fear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
103
2
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(116 citation statements)
references
References 19 publications
10
103
2
1
Order By: Relevance
“…Rabbits without an innate fear of foxes have an often-fatal anxiety disorder. However, even fear of snakes is not innate in primates but is only a cue especially conducive to fear conditioning (Mineka, Keir, & Price, 1980). Classical conditioning of emotions allows organisms to experience affect that slightly anticipates an event.…”
Section: Regulation Of Emotion Elicitationmentioning
confidence: 99%
“…Rabbits without an innate fear of foxes have an often-fatal anxiety disorder. However, even fear of snakes is not innate in primates but is only a cue especially conducive to fear conditioning (Mineka, Keir, & Price, 1980). Classical conditioning of emotions allows organisms to experience affect that slightly anticipates an event.…”
Section: Regulation Of Emotion Elicitationmentioning
confidence: 99%
“…Observational conditioning or social referencing may also be particularly relevant for understanding habituation in the sense that they involve the ability to attribute another's behavioural response to an external event (Feinman et al 1992 Although examples of observational conditioning or social referencing in the wild are scarce, captive studies have revealed the relevance and importance of these mechanisms during the developmental stages of nonhuman primates. For example, in a classic study, Mineka et al ( 1984 ) demonstrated that naïve captive rhesus monkeys showed no initial fear of snakes, but quickly learned to fear them by observing the responses of their (wild-born) parents. In a follow-up study, it was demonstrated that these learned responses were acquired more easily for biologically relevant than irrelevant stimuli.…”
Section: Habituation As Social Learningmentioning
confidence: 99%
“…Various mechanisms have been discerned within social learning, including imitation, stimulus enhancement, observational conditioning, and emulation (Sherry and Galef 1984 ;; Mineka et al 1984 ;; Tomasello 1990 ;; reviewed by Whiten and Ham 1992 ). Research on social learning has a distinguished history, starting with early reports based on anecdotal observations of natural behaviour (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The method was adapted from Mineka and her colleagues (Mineka et al, 1980;Mineka, 1987) and is identical to that reported previously . On each trial, the monkeys were allowed to reach for and to procure a food reward that had been placed on top of the clear box.…”
Section: Behavioral Testing Proceduresmentioning
confidence: 99%